2016
DOI: 10.1051/0004-6361/201628365
|View full text |Cite
|
Sign up to set email alerts
|

A model of short-lived outbursts on the 67P from fractured terrains

Abstract: Aims. We develop a physical model to explain the potent outbursts that occurred in the fractured terrain of comet 67P near perihelion, and predict its temporal characteristics. Methods. The feasibility of the proposed mechanism is studied using a numerical model accounting for the relevant microscopic/macroscopic processes. We rely on the thermophysical, compositional, and geo-morphological data from the published measurements of respective instruments on board Rosetta. Results. The key idea of this novel mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…For any bona fide parameter set the layer above the CO2 sublimation front amounts to several decimetres. The depth of CO is considerably larger because of its very low sublimation temperature and should be at least several meters (Skorov et al 2016). Even centimetre sized aggregates may still contain water ice if the effective pore size is in the 100 µm or smaller range.…”
Section: The Dichotomy Of the Gas Coma Com-positionmentioning
confidence: 99%
“…For any bona fide parameter set the layer above the CO2 sublimation front amounts to several decimetres. The depth of CO is considerably larger because of its very low sublimation temperature and should be at least several meters (Skorov et al 2016). Even centimetre sized aggregates may still contain water ice if the effective pore size is in the 100 µm or smaller range.…”
Section: The Dichotomy Of the Gas Coma Com-positionmentioning
confidence: 99%
“…That the outbursts occurred most often at either early morning or afternoon indicates that they could have been triggered by thermal stress. Alternatively, the sudden opening of a fracture or crack, also because of thermal stress, could also lead to a violent sublimation of the super-volatile ices buried in the deep interior according to Skorov et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…3The most important cause of a potential temperature increase above 30 K therefore is surface heating by insolation and subsequent conductive heat transfer from the surface to the interior. However, Skorov et al (2016) showed that ice sublimation in near-surface regions does not only cause substantial surface ablation, but also prevents an appreciable temperature increase below a depth of about 10 m. Thus, the active comet does not come to a thermal equilibrium and the center temperature stays close to the formation value. The exact knowledge of T i is not a precondition for our analysis in any case, as expounded in Appendix B.…”
Section: Initial Conditionsmentioning
confidence: 99%